2003
DOI: 10.1021/ja029786m
|View full text |Cite
|
Sign up to set email alerts
|

Use of Abasic Site-Containing DNA Strands for Nucleobase Recognition in Water

Abstract: Nucleobase recognition in water is successfully achieved by the use of an abasic site (AP site) as the molecular recognition field. We intentionally construct the AP site in DNA duplex so as to orient the AP site toward a target nucleobase and examine the complexation of 2-amino-7-methylnaphthyridine (AMND) with nucleobases at the AP site. AMND is found to selectively bind to cytosine (C) base with a 1:1 binding constant of >106 M-1, accompanied by remarkable quenching of its fluorescence. In addition to hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(114 citation statements)
references
References 13 publications
1
112
0
1
Order By: Relevance
“…The binding constants between pterin and G opposite the AP site were 1.2 × 10 4 M -1 for dSpacer and 2.6 × 10 4 M -1 for Spacer-C3, using a non-linear fitting method described previously. 9 As described in the results on the Tm measurements and fluorescence titration, we could obtain a more efficient binding ability by using Spacer-C3 as an AP site.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The binding constants between pterin and G opposite the AP site were 1.2 × 10 4 M -1 for dSpacer and 2.6 × 10 4 M -1 for Spacer-C3, using a non-linear fitting method described previously. 9 As described in the results on the Tm measurements and fluorescence titration, we could obtain a more efficient binding ability by using Spacer-C3 as an AP site.…”
Section: Resultsmentioning
confidence: 94%
“…[8][9][10][11][12][13][14] We have recently proposed a new method for SNPs typing based on fluorescent ligands with hydrogen-bond ability in combination with the use of an apurinic or apyrimidinic site, i.e. an AP site, as a molecular recognition field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Teramae's group has designed and synthesized a series of environmentally sensitive fluorescent probes which bind selectively to AP sites in ds-DNA. The binding was manifested by either fluorescence quenching or enhancement [9][10][11][12][13][14]. Wu et al reported an AP site selective fluorescent probe, sanguinarine with a large emission shift [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been developed for detecting the presence of these cytotoxic DNA lesions. Most techniques require irreversible modifications of isolated DNA , whereas others use non-natural nucleobase analogs [77][78][79][80][81][82][83][84][85][86][87][88][89] and only a few use 2AP to investigate the stacking ability of a base opposite an abasic site [90][91][92] . Fluorescent nucleobase analogs that positively sense the presence of abasic sites could provide useful nondestructive tools for the detection of such important DNA defects.…”
Section: Introductionmentioning
confidence: 99%